2011
DOI: 10.1152/ajpcell.00124.2010
|View full text |Cite
|
Sign up to set email alerts
|

Muscle-specific overexpression of NCOATGK, splice variant of O-GlcNAcase, induces skeletal muscle atrophy

Abstract: The protein O-linked β-N-acetylglucosamine (O-GlcNAc) modification plays an important role in skeletal muscle development and physiological function. In this study, bitransgenic mice were generated that overexpressed NCOAT(GK), an O-GlcNAcase-inactive spliced variant of the O-GlcNAcase gene, specifically in skeletal muscle using the muscle creatine kinase promoter. Expression of the chimeric enhanced green fluorescent protein-NCOAT(GK) transgene caused an increase of cellular O-GlcNAc levels, along with the ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 57 publications
0
18
0
Order By: Relevance
“…This excessive and mostly durable O‐GlcNAcylation on some proteins may modify their function and stability and promote the activation of muscle wasting process. Furthermore, in support of a role of OGA decrease in GC‐induced atrophy, a study has demonstrated that the overexpression of an inactive variant of OGA in transgenic mice causes muscle atrophy, as well as accumulation and activation of proapoptotic factors [Huang et al, ].…”
Section: Discussionmentioning
confidence: 99%
“…This excessive and mostly durable O‐GlcNAcylation on some proteins may modify their function and stability and promote the activation of muscle wasting process. Furthermore, in support of a role of OGA decrease in GC‐induced atrophy, a study has demonstrated that the overexpression of an inactive variant of OGA in transgenic mice causes muscle atrophy, as well as accumulation and activation of proapoptotic factors [Huang et al, ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, over-expression of OGT in muscle and adipose tissue causes insulin resistance and impairs glucose transport, respectively [21] , [22] . In addition, overexpression of OGA, which eliminates O-GlcNAcylation, impairs myogenesis and induces muscle atrophy [23] , [24] . These findings suggest that O-GlcNAcylation may be part of a complex signaling mechanism within skeletal muscle that is responsible for monitoring cellular nutrient availability and conveying this information to downstream targets to induce metabolic adaptation.…”
Section: Introductionmentioning
confidence: 99%
“…By the way, through OGA manipulation in C2C12 cells, O-GlcNAcylation seemed to be a negative regulator of the myogenesis. This conclusion is reinforced by the overexpression of an inactive OGA variant and the increase of O-GlcNAcylation in a rat model inducing skeletal muscle atrophy ( 116 ). In contrast, a skeletal muscle specific OGT knockout in mice, leading to a global decrease of O-GlcNAcylation in the tissue, did not induce muscle hypertrophy ( 65 ).…”
Section: O-glcnacylation and Skeletal Muscle Dysfunctionsmentioning
confidence: 97%